2013
DOI: 10.1111/jbg.12052
|View full text |Cite
|
Sign up to set email alerts
|

Consequences for diversity when animals are prioritized for conservation of the whole genome or of one specific allele

Abstract: When animals are selected for one specific allele, for example for inclusion in a gene bank, this may result in the loss of diversity in other parts of the genome. The aim of this study was to quantify the risk of losing diversity across the genome when targeting a single allele for conservation when storing animals in a gene bank. From a small Holstein population, genotyped for 54,001 SNP loci, animals were prioritized for a single allele while maximizing the genomewide diversity using optimal contribution se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…They furthermore showed that restricting the increase in similarity at specific regions would result in an increase in similarity for the rest of the genome. This was also described by Engelsma et al [296] and Roughsedge et al [297]. By including a constraint on the increase in similarity for the rest of the genome, this increase could be limited, although it was still higher than when no region-specific management was applied [82].…”
Section: Region-specific Diversity Managementsupporting
confidence: 53%
See 1 more Smart Citation
“…They furthermore showed that restricting the increase in similarity at specific regions would result in an increase in similarity for the rest of the genome. This was also described by Engelsma et al [296] and Roughsedge et al [297]. By including a constraint on the increase in similarity for the rest of the genome, this increase could be limited, although it was still higher than when no region-specific management was applied [82].…”
Section: Region-specific Diversity Managementsupporting
confidence: 53%
“…Various studies have stressed the potential benefit of maintaining diversity in specific regions of the genome, such as the Major Histocompatibility Complex (MHC) or regions associated with inbreeding depression [82,295,296]. With an approach like SDP, it is technically possible to perform region-specific diversity management.…”
Section: Region-specific Diversity Managementmentioning
confidence: 99%
“…Selection may directly cause changes in the frequency of major and minor alleles. Significance of frequencies of such alleles in the assessment of genetic diversity has been the object of various studies (Kaur et al, 2014;Engelsma et al, 2013), because they are an indicator of genetic variability and polymorphism in the observed locus (Singh et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In the cases of adaptively neutral loci, genetic drift has a significant role on the distribution of allelic frequencies. The importance of major and minor allele frequencies in genetic diversity estimation were subjects of various studies (De la Cruz & Raska, 2014; Kaur et al, 2014;Engelsma et al, 2013).…”
mentioning
confidence: 99%